2008
DOI: 10.1016/j.bbagen.2008.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Studies with leucine, β-hydroxybutyrate and ATP citrate lyase-deficient beta cells support the acetoacetate pathway of insulin secretion

Abstract: We hypothesized that contrasting leucine with its non-metabolizable analog 2-aminobicyclo[2,2,1]heptane-2-carboxylic acid (BCH) might provide new information about metabolic pathways involved in insulin secretion. Both compounds stimulate insulin secretion by allosterically activating glutamate dehydrogenase, which enhances glutamate metabolism. However, we found that leucine was a stronger secretagogue in rat pancreatic islets and INS-1 cells. This suggested that leucine's metabolism contributed to its insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 29 publications
(46 reference statements)
4
42
0
Order By: Relevance
“…Most AAs, including leucine, acutely stimulate insulin secretion from pancreatic b cells in a dose-and glucosedependent manner (Liu et al 2008), and leucine stimulates insulin secretion by serving as both a metabolic fuel and an allosteric activator of glutamate dehydrogenase , MacDonald et al 2008). Leucine and its transaminated product a-ketoisocaproate may also affect insulin secretion via direct inhibition of b-cell ATP-regulated potassium channel currents .…”
Section: Introductionmentioning
confidence: 99%
“…Most AAs, including leucine, acutely stimulate insulin secretion from pancreatic b cells in a dose-and glucosedependent manner (Liu et al 2008), and leucine stimulates insulin secretion by serving as both a metabolic fuel and an allosteric activator of glutamate dehydrogenase , MacDonald et al 2008). Leucine and its transaminated product a-ketoisocaproate may also affect insulin secretion via direct inhibition of b-cell ATP-regulated potassium channel currents .…”
Section: Introductionmentioning
confidence: 99%
“…They are produced by the liver and used peripherally as energy sources for various organs, particularly the skeletal muscle and brain, under conditions that include starvation, limited carbohydrate availability, and the neonatal period (41). AA participates in various biological processes that do not involve 3HB, including insulin release in vitro (42), generation of free oxygen radicals (43)(44)(45), and lipid peroxidation (46). AA also stimulates chaperone-mediated autophagy (47) and down-regulates the expression of ATP-binding cassette transporter A1 (ABCA1) in vitro (48).…”
mentioning
confidence: 99%
“…This model has it pros and cons, which have been reviewed extensively elsewhere [12,48]. Our recent studies [25,38], as well as others [49][50][51] have now shown a consistent lack of evidence for a direct role of malonyl-CoA in regulation of GSIS, whereas its potential role in lipid-mediated potentiation of GSIS remains a possibility. Our results showing that inhibition of DIC NADPH has also been suggested to play an important role as a metabolic messenger regulating insulin release [15,17,19,[22][23][24]52].…”
Section: Discussionmentioning
confidence: 88%